2005
DOI: 10.1007/s10211-005-0107-7
|View full text |Cite
|
Sign up to set email alerts
|

Can the acoustic adaptation hypothesis predict the structure of Australian birdsong?

Abstract: The acoustic adaptation hypothesis (AAH) predicts that long-distance signals will be structured so as to maximize their transmission fidelity. Previous studies testing the hypothesis on birdsong have provided equivocal support. The best support comes from large-scale comparative studies and those studies where habitat is characterized as "open" versus "densely vegetated." In the first case, sufficient statistical power is present to detect even small effects on song structure, whereas in the later case the "ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 28 publications
(48 reference statements)
0
28
1
1
Order By: Relevance
“…However, the occurrence of vocal learning did not seem to play a determinant role in adjustment of call structure to the environment. For instance, predictions were verified in a group of tinamous species (Bertelli & Tubaro 2002) in which no evidence of vocal learning has been found, while they were not verified in Indigo Bunting (Hylton & Godard 2001) and a group of 121 Australian songbird species (Blumstein & Turner 2005) which are song learners. These different factors (songs, passerines, vocal learning) which do not seem to influence environmentrelated variations suggest that environmental adaptations might have occurred independently over evolution in bird taxa.…”
Section: Methodological Pointsmentioning
confidence: 86%
“…However, the occurrence of vocal learning did not seem to play a determinant role in adjustment of call structure to the environment. For instance, predictions were verified in a group of tinamous species (Bertelli & Tubaro 2002) in which no evidence of vocal learning has been found, while they were not verified in Indigo Bunting (Hylton & Godard 2001) and a group of 121 Australian songbird species (Blumstein & Turner 2005) which are song learners. These different factors (songs, passerines, vocal learning) which do not seem to influence environmentrelated variations suggest that environmental adaptations might have occurred independently over evolution in bird taxa.…”
Section: Methodological Pointsmentioning
confidence: 86%
“…Vargas‐Salinas & Amézquita, ), birds (e.g. Saunders & Slotow, ; Blumstein & Turner, ) and mammals (e.g. Peters & Peters, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Bertelli & Tubaro (), the songs of tinamous living in open habitats were higher‐pitched and had a wider frequency bandwidth than those of their relatives living in closed habitats, in accordance with the AAH. However, Blumstein & Turner () and Saunders & Slotow () found only weak support of the AAH when examining spectral and temporal characteristics of songs and controlling for phylogenetic effect in 121 and 40 bird species, respectively. Peters & Peters () examined long‐distance roars of 27 species of Felidae (taking into account body size and phylogenetic relationships) and found that their dominant frequency was lower in open than in closed habitats, contradicting the AAH prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Morton 1975;Waser and Waser 1977;Wallschläger 1981Wallschläger , 1985Brown and Waser 1988;Wiley 1991;Brown and Gomez 1992;Brown et al 1995;Daniel and Blumstein 1998;Slabbekoorn and Smith 2002;Ryan and Kime 2003;Saunders and Slotow 2004;Blumstein and Turner 2005;Boncoraglio and Saino 2007). Data on diverse vertebrate taxa support this hypothesis (Morton 1975;Gish and Morton 1981;Wallschläger 1980Wallschläger , 1982Wallschläger , 1985Wallschläger and Nikolskij 1985;Masters 1991;Saunders and Slotow 2004;Slabbekoorn 2004;Seddon 2005;Nicholls and Goldizen 2006;Tubaro and Lijtmaer 2006), while in other taxa it is only supported weakly (Blumstein and Turner 2005;Boncoraglio and Saino 2007) or is not supported (Daniel and Blumstein 1998;Kime et al 2000;Saunders and Slotow 2004). In all types of natural habitat, the height of the signal source and that of the receiver are important factors in acoustic communication (Kime et al 2000;Slabbekoorn 2004), although the relative importance of the elevation above ground may be different for sender and receiver (Mathevon et al 2005).…”
Section: Acoustic Adaptation Hypothesis (Aah)mentioning
confidence: 99%